Uma Investigação sobre Técnicas de Data Augmentation Aplicadas a Tradução Automática Português-LIBRAS - Silva, Marcos André Bezerra da; Lima, Manuella Aschoff C. B.; Silva, Diego Ramon Bezerra da; Souza, Daniel Faustino L. de; Costa, Rostand Edson O.; Araújo, Tiago Maritan U. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2024)
The automatic translation from Portuguese to LIBRAS is extremely important for accessibility and inclusion of deaf individuals in society, but the scarcity of data and the high cost of building an authentic corpora pose significant challenges. Data Augmentation in Neural Machine Translation is the process of generating synthetic sentences to increase the quantity and diversity of the training set. This work investigates the use of data augmentation techniques to improve the performance of Portuguese-LIBRAS automatic translation using the BLEU metric. Among the techniques analyzed, back-translation and its combination with synonym substitution using part-of-speech tagging stood out as the most effective in enhancing the translation model and can be used to increase the diversity of underrepresented datasets.